Controllable Synthesis of Submillimeter Single-Crystal Monolayer Graphene Domains on Copper Foils by Suppressing Nucleation - Wang, Hong; Wang, Guanzhong; Bao, Pengfei; Yang, Shaolin; Zhu, Wei; Xie, Xing; Zhang, Wen-Jun (Journal of the American Chemical Society, 2012)
Submillimeter single-crystal monolayer and multilayer graphene domains were prepared by an atmospheric pressure chemical vapor deposition method with suppressing nucleation on copper foils through an annealing procedure. A facile oxidation visualization method was applied to study the nucleation density and morphology of graphene domains on copper foils. Scanning electron microscopy, transmission electron microscopy, atomic force microscopy, polarized optical microscopy, and Raman spectra showed that the submillimeter graphene domains were monolayer single crystals.